POLA EDUKASI POLITIK PENCEGAHAN GOLPUT DAN POLITIK IDENTITAS AKUN DETIKCOM DI MEDIA SOSIAL FACEBOOK - Muhammad Ichsanul Amal; Izomiddin Izomiddin; Ahmad Muhaimin (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACT This study discusses Political Educational Patterns Of Golput Prevention And Detikcom Account Identity Policies On Facebook Social Media. The purpose of this study was to determine Political Educational Patterns Of Golput Prevention And Detikcom Account. The objects in this study are the detikcom Facebook account and the Facebook community who comment on posts on detikcom. The theory used is the theory of Political Education by M Nur Khoiron because this theory can discuss patterns of political education on Facebook social media. The type of research used is analysis and qualitative approach with Documentation and Literature Study methods. The data sources of this study are parties directly involved in political education pattern detikcom accounts on Facebook social media, data are collected and analyzed through documentation and literature studies. The results of the study show that there are two patterns of political education carried out by the Detikcom account, namely political education about abstentions and identity politics and their prevention. The pattern of political education for the Detikcom account on Facebook social media is that the work system often provides political education about abstentions and identity politics and their prevention that occurs during political momentum such as the political year which aims to provide insight and understanding of the importance of voting rights and preventing polarization in society.